ANALISIS PENGARUH MOTIVASI KONSUMEN, KEPERCAYAAN KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN DENGAN SIKAP KONSUMEN SEBAGAI VARIABEL MODERASI - Abdullah, Abdullah; Kuswardani, DC; Wardoyo, Paulus (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2023)
This study aims to determine and analyze consumer attitude as a moderation variable on the effect of consumer motivation and consumer trust on property purchasing decisions. This study uses primary data by distributing questionnaires to respondents, namely the owner of Green Taman Asri housing complex. Sampling is done using the NonProbability Sampling method and the sampling technique using sensus Sampling. The analysis in this study used a moderation regression analasis test. The results of this study indicate that consumer motivation consumer trust have a positive and significant effect on purchasing decision. Meanwhile consumer attitude has a positive as a moderating variable has a significant positive effect on the effect of consumer motivation and consumer trust on property purchasing decisions, with a coefficient of determination (Adjusted R Square) of 0.799 which means that together independent variables explain the purchase decision by 79.9%, while the remaining 20.1% is influenced by other variables